-3x-9y=9

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Add 3x to both sides of the equation.

-9y=9+3x

Divide each term by -9 and simplify.

Divide each term in -9y=9+3x by -9.

-9y-9=9-9+3x-9

Cancel the common factor of -9.

Cancel the common factor.

-9y-9=9-9+3x-9

Divide y by 1.

y=9-9+3x-9

y=9-9+3x-9

Simplify 9-9+3x-9.

Simplify each term.

Divide 9 by -9.

y=-1+3x-9

Cancel the common factor of 3 and -9.

Factor 3 out of 3x.

y=-1+3(x)-9

Cancel the common factors.

Factor 3 out of -9.

y=-1+3×3⋅-3

Cancel the common factor.

y=-1+3×3⋅-3

Rewrite the expression.

y=-1+x-3

y=-1+x-3

y=-1+x-3

Move the negative in front of the fraction.

y=-1-x3

y=-1-x3

Reorder -1 and -x3.

y=-x3-1

y=-x3-1

y=-x3-1

Rewrite in slope-intercept form.

y=-13x-1

y=-13x-1

Using the slope-intercept form, the slope is -13.

m=-13

Find the Slope -3x-9y=9